Econometrics: Alchemy or science? Essays in econometric methodology - Hendry, D (Oxford University Press, 2000)
Eighteen previously published papers on methodology, from the period 1974 to 1985, provide an overview of the development of the field and are integrated by commentary on the motivations, personalities, and ideas central to this development. Papers discuss whether econometrics is alchemy or science; stochastic specification in an aggregate demand model of the United Kingdom; testing dynamic specification in small simultaneous systems and an application to a model of building-society behavior in the United Kingdom; dynamic specification; the time-series approach to econometric model building; serial correlation as a convenient simplification; an empirical application and Monte Carlo analysis of tests of dynamic specification; econometric modeling of the aggregate time-series relationship between consumers' expenditure and income in the United Kingdom; liquidity and inflation effects on consumers' expenditure; interpreting econometric evidence and the behavior of consumers' expenditure in the United Kingdom; predictive failure and econometric modeling in macroeconomics and the transactions demand for money; monetary economic myth and econometric reality; the structure of simultaneous equations estimators; AUTOREG--a computer program library for dynamic econometric models with autoregressive errors; exogeneity; the formulation of empirical models in dynamic econometrics; the econometric analysis of economic time series; and econometric modeling and the consumption function in retrospect. Includes a postscript on the econometrics of PC-GIVE. A new epilogue explains the recent advances in computer automation of model selection. Hendry is Leverhulme Personal Research Professor of Economics and Fellow of Nuffield College, Oxford University. Bibliography; index.